Effect of inhibitor gases on hydrogen flame propagation in a confined tee pipe (Part I) - Emami, Sina Davazdah (Elsevier Ltd, 2016)
Hydrogen is a promising fuel for the future. In recent years it has been successfully utilised in industries, particularly in refineries and petrochemicals. In previous studies, the effect of inhibitors on hydrogen explosion behaviour has been investigated in different systems, yet only scarce data are available. Therefore, experimental study is carried out to investigate the effects of argon, nitrogen and carbon dioxide on hydrogen/air explosion in a branched pipe configuration. The fuel/air mixtures were ignited at three different ignition positions, A, B and D. The results show that, when ignited at the furthest distance (position A), the tee junction area is most vulnerable to the critical pressure impact of gas explosion. However, no similar trend was observed at the other ignition positions. In addition, mixtures with the compositions 95% H-2-2.5% Ar-2.5% N-2/air, 95% H-2-5% N-2/air, H-2/air and 95% H-2-5% Ar/air showed higher risks due to the higher diffusivity ratio and the associated rate of pressure rise. This phenomenon is highlighted in the discussion part of this paper. The results show that mixtures with CO2 lead to lower severity than other compositions (similar to 50% reduction), as the average recorded maximum flame speed for this particular mixture was lower at all of the ignition points. This suggests that the effectiveness of the inhibitors should be in the order of Ar < N-2 < CO2.